Enhancing work life through social cognition: the effect of SCIT in bipolar disorder - Anaforoglu Bikmaz, Zeynep; Mackali, Zeynep; Cakir, Sibel (Frontiers in Psychology, 2025)
ObjectivesThis study aimed to investigate the effectiveness of social cognition and interaction therapy (SCIT) in improving occupational functioning in individuals diagnosed with bipolar disorder I (BD-I). The effects of SCIT intervention with standard treatment methods were investigated on social cognition and functioning effects, which are often negatively affected in patients with BD-I.MethodsThe research involved 28 participants, allocated into two groups: An experimental group (n = 12) receiving SCIT for 8 weeks alongside standard treatments (pharmacotherapy and psychiatric interviews), and a control group (n = 16) undergoing standard treatment without additional interventions. Outcome measures were assessed using a suite of tools, including the Hamilton Depression Rating Scale (HDRS), Young Mania Rating Scale (YMRS), Eyes Test (ET), Metacognition Scale (MCI), Internalized Stigma of Mental Illnesses (ISMI), and Functioning Assessment Short Test (FAST). Given the small sample size, non-parametric tests were employed for data analysis. Analyses were conducted using the Mann–Whitney U test and Wilcoxon test for comparisons between the experimental and control groups and within groups. Also, the effects of the intervention on social cognition, occupational functioning and resistance to stigmatization were dealt.ResultsThe findings revealed that participants in the experimental group showed significant improvements in social cognition and occupational functioning after SCIT compared to the control group. However, the levels of stigmatization experienced by individuals as a result of ISMI measurements were significantly lower in the SCIT group compared to the control group.ConclusionThe study concludes that SCIT can be an effective intervention for enhancing certain psychosocial and cognitive functions in individuals with BD-I, thereby improving their occupational functioning. Nevertheless, the persistent levels of stigma indicate the need for additional strategies to address the broader challenges faced by individuals with BD-I in terms of societal perception and self-stigmatization.